American gospel : a novel - Enger, Lin (University of Minnesota Press, 2020)
"On a small farm beside a lake in Minnesota's north woods an old man is waiting for the Rapture, which God has told him will happen in two weeks, on August 19, 1974. When word gets out, Last Days Ranch becomes ground zero for The End, drawing zealots, curiosity seekers, and reporters- among them the prophet's son, a skeptical New York writer suddenly caught between his overbearing father and the news story of a lifetime. Into the mix comes Melanie Magnus, a glamorous actress who has old allegiances to both father and son. Meanwhile, Nixon's resignation has transfixed the nation... Lin Enger draws us into these disparate yet inextricably linked lives, each enacting a part in a drama forever being replayed and together moving toward a conclusion that will take all of them- and us- by surprise. "--Dust jacket flap.